2009
DOI: 10.1002/qua.560300816
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glyoxalase I in vitro by coumarin and coumarin derivatives

Abstract: Previous reports from these laboratories on the inhibition of glyoxalase I (S-lactoyl-glutathione methylglyoxal lyase, isomerizing; EC 4.4.1.5) (Glo I) have been presented for various flavones and other compounds. We report here the inhibition of Glo I by coumarin and various coumarin derivatives. Human red blood cell Glo I was purified 7000-fold and the concentration of various coumarins was determined for 50% inhibition (I,) of enzyme activity. These compounds resemble the transition state of the methylglyox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1158 Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1 IC 50 = 3.5 μM) and myricetin (human Glo1 IC 50 = 5 μM). 1159,1167 Further exploration of transition state mimetics was performed analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state based inhibitors is involved in metal coordination. 1171 A computational analysis of previously published transition state mimics, demonstrated that the most important motif for activity was a α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin.…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%
See 1 more Smart Citation
“…1158 Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1 IC 50 = 3.5 μM) and myricetin (human Glo1 IC 50 = 5 μM). 1159,1167 Further exploration of transition state mimetics was performed analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state based inhibitors is involved in metal coordination. 1171 A computational analysis of previously published transition state mimics, demonstrated that the most important motif for activity was a α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin.…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%
“…More active inhibitors included maltol (Glo1i-3, yeast Glo1, K i = ∼400 μM), squaric acid (Glo1i-4, human Glo1, IC 50 = 120 μM), and 2,3-dihydroxy-benzoic acid (Glo1i-5, IC 50 = 280 μM). , An expansion of potential transition state mimetics, including 2,3-dihydroxypyridine (Glo1i-6, human Glo1, IC 50 = 530 μM) and polyphenolic benzohydroxamic acids such as 2,3,4-trihydroxybenzohydroxamic acid (Glo1i-7, human Glo1, IC 50 = 210 μM), were reported . Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1, IC 50 = 3.5 μM) and myricetin (human Glo1, IC 50 = 5 μM). , Further exploration of transition state mimetics was performed by analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state-based inhibitors is involved in metal coordination . A computational analysis of previously published transition state mimics demonstrated that the most important motif for activity was an α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin .…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%